2019
DOI: 10.1093/asj/sjz248
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Increased Patient Satisfaction Following Liquid Formulation AbobotulinumtoxinA Treatment in Glabellar Lines: FACE-Q Outcomes From a Phase 3 Clinical Trial

Abstract: Background The FACE-Q patient-reported outcome assesses patient experiences/outcomes with aesthetic facial procedure. A recent trial of abobotulinumtoxinA (ASI, liquid-formulation) was the first to assess satisfaction with FACE-Q after glabellar-line (GL) injection. Objectives To evaluate patient-satisfaction with ASI for GL treatment using three FACE-Q scales: facial appearance, psychological well-being, and aging appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The results from the DBPC period were similar to those observed with the same 3 FACE-Q outcome measures during the previously mentioned single-cycle Phase III aboBoNT-A solution study. 11 Furthermore, in the present study, the magnitude of change observed compared with cycle baseline was consistent across repeated treatment cycles for each of the 3 FACE-Q scales. To the authors’ knowledge, this is the first study to report the impact of aboBoNT-A treatment on satisfaction as assessed by FACE-Q over repeat cycles in a prospective clinical study.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The results from the DBPC period were similar to those observed with the same 3 FACE-Q outcome measures during the previously mentioned single-cycle Phase III aboBoNT-A solution study. 11 Furthermore, in the present study, the magnitude of change observed compared with cycle baseline was consistent across repeated treatment cycles for each of the 3 FACE-Q scales. To the authors’ knowledge, this is the first study to report the impact of aboBoNT-A treatment on satisfaction as assessed by FACE-Q over repeat cycles in a prospective clinical study.…”
Section: Discussionsupporting
confidence: 70%
“…Full details of the FACE-Q scales and associated questions have been published previously. 11 , 13-15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent article by Dr Ascher and colleagues titled “Significantly Increased Patient Satisfaction Following Liquid Formulation AbobotulinumtoxinA Treatment in Glabellar Lines: FACE-Q Outcomes From a Phase 3 Clinical Trial” highlights the importance of patient-reported outcome (PRO) measures in facial aesthetic clinical trials. 1 Although we completely agree with the importance of PROs in assessing aesthetic conditions and treatments, we noted inaccurate claims that 2 PRO measures used for assessing outcomes with botulinum toxin type A (BoNTA), the Facial Line Outcomes (FLO) Questionnaire and the Facial Line Satisfaction Questionnaire (FLSQ), are not in alignment with FDA PRO guidance. Specifically, the authors stated:…”
mentioning
confidence: 82%
“…A recent Letter to the Editor by Dr Patel and colleagues, entitled “Facial Lines Outcomes (FLO-11) and Facial Line Satisfaction Questionnaire (FLSQ) Meet FDA PRO Guidance” 1 noted an inaccuracy in a statement in the introduction of our paper entitled, “Significantly Increased Patient Satisfaction Following Liquid Formulation AbobotulinumtoxinA Treatment in Glabellar Lines: FACE-Q Outcomes From a Phase 3 Clinical Trial.” 2 In our introduction, we reference 2 review articles by Morley et al 3 and Kosowski et al, 4 both of which note that very few patient-reported outcome (PRO) measures for aesthetic procedures are aligned with the recommendations for the development and validation of PRO measures defined in each review. As an example, we had referred to the US Food and Drug Administration (FDA) criteria for PRO measures, as discussed by Morley et al 3 Dr Patel and colleagues have highlighted that both of these reviews 3 , 4 in fact refer to the previous versions of these 2 measures, which have since been updated and developed in accordance with FDA PRO guidance.…”
mentioning
confidence: 99%